LRTM effect and electronic crystal imaging on silicon surface - Zhong-Mei Huang (Nature Portfolio, 2021)
Abstract Some interesting phenomena have been observed in the laser reflecting Talbot magnification (LRTM) effect discovered at first, in which the high-order nonlinear imaging and the plasmonic structures imaging occur. The LRTM effect images were obtained on the 1D and 2D photonic crystals fabricated by using nanosecond pulsed laser etching on silicon surface, where the high-order nonlinear imaging on the 1D and 2D photonic crystals was observed interestingly. The theory result is consistent with the experimental one, which exhibits that the suitable wave-front shape of injection beam selected in optical route can effectively enlarge the magnification rate and elevate the resolution of the Talbot image. Especially the periodic plasmonic structures on silicon surface have been observed in the LRTM effect images, which have a good application in the online detection of pulsed laser etching process. The temporary reflecting Talbot images exhibit that the electrons following with photonic frequency float on plasma surface to form electronic crystal observed on silicon at first, which is similar with the Wigner crystal structure.